as - Yosi Candra Triwahyuni (Global Accounting, 2024)
The reason of this think about is to illustrate the affect of capital escalated, productivity, liquidity, and capital structure on assess forcefulness. The subordinate variable in this inquire about is charge forcefulness, whereas the autonomous factors utilized in this investigate are capital escalated, benefit, liquidity and capital structure in nourishment and refreshment sub-sector fabricating companies recorded on the Indonesia Stock Trade period 2019 – 2022. The populace for this think almost was 43 companies. The data utilized for this think almost is assistant data where the test was chosen utilizing purposive analyzing strategy. The tests utilized in this consider were 56 tests. The data examination methodologies utilized in this think approximately were realistic estimations, classical doubts, and hypothesis testing utilizing SPSS frame 25 computer program application. The partial test results obtained in this research show that capital intensity, profitability and liquidity have no effect on tax aggressiveness, while capital structure has an effect on tax aggressiveness. The simultaneous test results obtained in this research show that capital intensity, profitability, liquidity and capital structure together influence tax aggressiveness.